BIM and construction health and safety : uncovering, adoption and implementation /: uncovering, adoption and implementation. (2023) - Golizadeh, Hamed; Banihashemi, Saeed, 1985-; Hon, Carol K. H; Drogemuller, Robin
No abstract available